Association of long COVID documentation with clinical outcomes among Veterans with diabetes - Pandora L. Wander; Elliott Lowy; Anna Korpak; Lauren A. Beste; Edward J. Boyko (PLoS ONE, 2025)
Objective To examine public health impacts of Long COVID on long-term hyperglycemia and metabolic health. Materials & Methods We conducted a retrospective cohort study using US Veterans Health Administration electronic health records data to examine associations of Long COVID documentation (International Statistical Classification of Diseases, Tenth Revision code U09.9) with clinical outcomes (number of primary care visits, receipt of new classes of glucose-lowering medications, weight change, hemoglobin A1c, initiation of insulin, initiation of dialysis, hospitalization, and mortality) among U.S. Veterans with diabetes (1 October 2021–1 October 2023; n = 1,896,080). Results Veterans were 69.7 years old on average at cohort entry, 6% female, and 1% had U09.9 documentation. Compared to Veterans without U09.9, those with U09.9 had 39% more primary care visits per year after the index date (incidence rate ratio [IRR] 1.36, 95%CI 1.36; 1.37), 21% more glucose-lowering medication classes added per year (IRR 1.21, 95%CI 1.18; 1.24), a 0.62 kg greater weight gain (95%CI 0.52; 0.72), a 0.10-point lower mean HbA1c (95%CI -0.12; -0.08), a 43% greater odds of starting insulin (odds ratio [OR] 1.43, 95%CI 1.32; 1.54), a 34% greater odds of starting dialysis (OR 1.34, 95%CI 1.11; 1.62), a 102% greater odds of VA hospitalization (OR 2.02, 95%CI 1.95; 2.09), and a 13% lower odds of mortality (OR 0.87, 95%CI 0.83; 0.91). Conclusions In Veterans with diabetes, Long COVID documentation was associated with greater medication use, odds of starting dialysis, and odds of hospitalization, but with lower odds of mortality. Individuals with Long COVID documentation did not have more weight gain or higher HbA1c, suggesting that adverse effects of Long COVID on medication changes and kidney function in persons with diabetes may be due to other factors. Future studies should examine mechanisms by which Long COVID might contribute to progression of kidney disease and more intensive diabetes treatment.